Espécies de adubos verdes potenciais para fitorremediação de solos contaminados com diuron, hexazinone e sulfometuron-methyl - Santos, Matheus Silva dos (Universidade Federal Rural do Semi-Árido, 2019)
Herbicide-contaminated soils pose a great risk to the environment and human health. Among the herbicides that present a potential risk of contamination are diuron, hexazinone and sulfometuron-methyl, which are widely used for weed control in sugarcane crop. Thus, in view of this problem, the objective of this study was to evaluate the potential for remediation of green manure species C. ensiformes, S. aterrimum, R. sativus, C. spectabilis, Lupinus albus and P. glaucum in reducing negative impacts on the environment. environment and subsequent crops caused by residues of the herbicides diuron, hexazinone and sulfometuron-methyl. To carry out the studies, soils were contaminated with the three radiolabelled herbicides individually before sowing the green manure species. At 14 days after emergence (DAE) phytotoxicity assessments were performed using the adapted European Weed Research Council (EWRC) rating scale (Rolim, 1989). For the study of absorption and translocation the plants were removed from the pots, cut into root, stem, cotyledonary leaves, old leaves and new leaves. The soil and each plant part were oxidized separately using a biological oxidizer and radioactivity measured on a liquid scintillation spectrometer. Root absorption and translocation of the herbicides 14C-diuron, 14C-hexazinone and 14C-sulfometuron-methyl behave differently among the green manure species analyzed. The six species of green manure studied had the greatest potential to remedy hexazinone contaminated soils. The species C. ensiformes has higher efficiency for hexazinone absorption.
Monografia
Keywords: Herbicidas radiomarcados;; Descontaminação de solo; Remediação; Absorção radicular; Ttranslocação; Radiolabelled herbicides; Soil decontamination; Remediation; Root absorption; Translocation; CIENCIAS AGRARIAS::AGRONOMIA